Multipurpose machine for sieving "ogi" slurry (2011)
A multipurpose machine for sieving 'Ogi' (ground com slurry) and other applicable grain slurry comprises the sieving container (003) which receives water frorn an external water unit {OI2) and the slurry 'Ogi' to be sieved through a hopper. Sieving is achieved by an arrangement of vibration and sitting mechanism (&13) which is electrically driven (009) by a motor. Depending on the type of ground grain slurry, interchangeable assembly of sieving arrangement are applied within the sieving unit to account for the multipurpose usage of the machine.